Restoration of a Nonvital Tooth with Fiber Reinforce Composite (Wallpapering Technique) - Sara Valizadeh; Ladan Ranjbar Omrani; Simone Deliperi; Farzaneh Sadeghi Mahounak (Case Reports in Dentistry)
Introduction. Reconstruction of endodontically treated tooth (ETT) is one of the greatest challenges in dentistry. Clinical success of fiber reinforcement composite (FRC) restorations in ETT depends on many factors like remaining tooth structure, knowing advantages of adhesive dentistry besides its drawbacks, and the correct use of fibers in combination with resin composite. Case Report. This article presents a case in which fibers have been used in composite buildup in order to increase the toughness and strength of the ETT direct restoration. In addition, this technique does not require root canal enlargement to eliminate the risk of root perforation. Also, this one visit treatment can be helpful for patients that could not pay the cost of indirect restoration and/or have no time. Conclusion. It seems in selected patients with special considerations, FRC composite restoration is valid alternatives for indirect restoration.